1985
DOI: 10.1007/bf01655277
|View full text |Cite
|
Sign up to set email alerts
|

Accessory spleens: Clinical significance with particular reference to the recurrence of idiopathic thrombocytopenic purpura

Abstract: One of the important stages during splenectomy is the search for accessory spleens. The average frequency of accessory spleens is an estimated 11%. In our own material in 611 patients who had splenectomy in hematological disorders, accessory spleens were found in 110 patients (18%). The surgical anatomy, embryology, and clinical significance of the accessory spleens, with particular reference to the recurrence of idiopathic thrombocytopenic purpura (ITP) are discussed. The group of 177 patients with ITP treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
3
7

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 19 publications
3
76
3
7
Order By: Relevance
“…That and the low mean intraoperative bloodloss indicates that the surgeons took perfectly advantage of the video assisted technique such as better view and more precise dissection. (6). In the present paper the rate of AS found by ultrasound or by intraoperative diagnosis was 19.2% and therefore is considerable low in comparison with published data: up to 30% in patients with hematologic diseases (5).…”
Section: G Szinicz and A Zerzcontrasting
confidence: 61%
“…That and the low mean intraoperative bloodloss indicates that the surgeons took perfectly advantage of the video assisted technique such as better view and more precise dissection. (6). In the present paper the rate of AS found by ultrasound or by intraoperative diagnosis was 19.2% and therefore is considerable low in comparison with published data: up to 30% in patients with hematologic diseases (5).…”
Section: G Szinicz and A Zerzcontrasting
confidence: 61%
“…Lack of immediate and satisfactory post-splenectomy result or recurrence of thrombocytopenia are almost entirely connected with the remaining splenic tissue (7)(8)(9)(10)(11)(12)(13). Most authors, despite the use of different imaging techniques (ultrasonography, US; classic and spiral Computed Tomography, CT; and scintigraphy) underline the lack of reliable ways of preoperative assessment of ectopic splenic tissue (9, 10, 14, 15).…”
Section: Discussionmentioning
confidence: 99%
“…Targarona et al (20) reported the findings of an accessory spleen in 33% of the patient who had not clinical improvement after laparoscopic splenectomy for treatment of ITP. An association between the presence of missed accessory splenic tissue and recurrent or unresolved ITP after initial splenectomy has been reported (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nebenmilzen können völlig unbemerkt bleiben oder klinische Bedeutung erlangen, wenn sie z.B. Lymphome oder Metastasen [19] oder einen Tumor des Magens [20][21][22], des Kolons, des Zwerchfells, der Niere, der Nebenniere [23,24] oder des Pankreas vortäuschen. Außerdem können sie durch Stieldrehung [25], Spontanrupturen [26,27], Infarkt oder Blutung [28] eine akute Bauchsymptomatik hervorrufen.…”
Section: Diskussionunclassified